ANALISIS SEMIOTIKA PESAN KEBAHAGIAAN PADA LAGU; APA YANG TAK BISA - Aghil Nugraha; Cindenia Puspasari; Muchlis; Muhammad Ali (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
Music serves not only as entertainment but also as a medium of communication that conveys messages and meanings through song lyrics. One song that reflects philosophical values of happiness is Apa yang Tak Bisa by Rumahsakit. This study aims to analyze the meaning of happiness messages contained in the song lyrics using Roland Barthes' semiotic approach. This research employed a descriptive qualitative method with data collected through observation, documentation, and literature review. The analysis was conducted at the levels of denotation, connotation, and myth. The findings reveal that the lyrics portray happiness as the ability to accept life's realities, exercise self-control, and express gratitude for God's will. At the denotative level, the lyrics describe the experience of not always obtaining what one desires. At the connotative level, they convey the importance of sincerity, gratitude, and self-control in facing life. At the mythological level, the lyrics reinforce the belief that every divine decree is part of God's best plan for human beings. This study concludes that Apa yang Tak Bisa functions not only as entertainment but also as a medium for communicating philosophical values related to happiness, acceptance of life, and trust in destiny.